Competitiveness analysis on Vietnam tourism in relation with Asean countries at present - Vu, Chien Thang (H. : ĐHQGHN, 2019)
This paper aims at analyzing aspects that are affecting the competitiveness of Vietnam tourism in relation with other Southeast Asian (ASEAN) countries. The issues to be addressed are as follows: (1) the international tourist market share of Vietnam in ASEAN; (2) Vietnam’s position in competitiveness ranking by the World Economic Forum (WEF); (3) Effectiveness of tourism in Vietnam in relation to ASEAN countries.